NON-HODGKIN'S LYMPHOMAS IN THE ELDERLY: STRUCTURAL FEATURES, CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS - Karimova M.N; Karshiboev A.U; Esankulova B.S; Makhmudova I.A. (Scholar Express Journals, 2024)
Non-Hodgkin's lymphomas (NHL) are a group of malignant tumors that develop from lymphoid tissue. In older people, the incidence of NHL increases. The study, conducted between 2021 and 2024, analyzed data from 169 older patients with NHL. The age of the patients ranged from 60 to 86 years, the average age was 69.4 years. The ratio of men and women was equal. The findings are consistent with other studies that have shown that older patients with NHL are more likely to have aggressive forms of the disease, delay presentation to medical care, and have a poorer prognosis. The findings highlight the importance of early diagnosis and treatment of NHL in older patients. Early treatment may improve the prognosis of the disease.
Keywords: Non-Hodgkin's lymphomas; elderly people; structure